2002
DOI: 10.2149/tmh1973.30.301
|View full text |Cite
|
Sign up to set email alerts
|

An Endemic Human Infection with Heterophyes nocens Onji et Nishio 1916 at Mikkabi-cho, Shizuoka, Japan.

Abstract: Human Heterophyes nocens infection was confirmed in 2 areas of Mikkabi-cho, Shizuoka Prefecture where high prevalence of Metagonimus yokogawai infection had been reported. The total prevalence showed 9.6% by stool examination. Among the patients, the older age's males predominated, and theinfection within the same family was often observed. Adult worms were collected from stool samples of the patients after treatment with praziquantel. The worms were identified as H. nocens with morphological characteristics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…In this study, humans showed a prevalence of heteropyhid eggs of 13.3% (Table 2), which is consistent with the 13.5% reported in Egypt (El-Morshidy et al 1994) and 9.6% in Japan (Kingo et al 2002). This prevalence is, however, lower than 42.9% reported in Korea (Chai et al 1994), 33.8% in Egypt (Abou-Basha et al 2000, and 100% in Vietnam (Dung et al 2007), but higher that those recorded in Egypt, 5% ) and 5.1% (Rifaat et al 1980).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, humans showed a prevalence of heteropyhid eggs of 13.3% (Table 2), which is consistent with the 13.5% reported in Egypt (El-Morshidy et al 1994) and 9.6% in Japan (Kingo et al 2002). This prevalence is, however, lower than 42.9% reported in Korea (Chai et al 1994), 33.8% in Egypt (Abou-Basha et al 2000, and 100% in Vietnam (Dung et al 2007), but higher that those recorded in Egypt, 5% ) and 5.1% (Rifaat et al 1980).…”
Section: Discussionsupporting
confidence: 91%
“…In the Republic of Korea, prevalences ranging from 10% to 70% were detected among residents in southwestern coastal areas, including islands [2,189]. In Japan, human H. nocens infections were reported from Kochi, Chiba, Yamaguchi, Chugoku, Hiroshima, and Shizuoka Prefectures [190,191].…”
Section: Haplorchis Vanissimusmentioning
confidence: 99%
“…In South Korea, residents of southwestern coastal areas and islands showed 10–70% egg-positive rates (Chai et al ., 2004 , 2009 ). In Japan, Kochi, Chiba, Yamaguchi, Chugoku, Hiroshima and Shizuoka Prefectures were the places where human infections were recorded (Kino et al ., 2002 ). Diagnosis is based on the recovery of eggs in fecal examinations, but eggs should be differentiated from those of other heterophyids and small liver flukes.…”
Section: Intestinal Flukesmentioning
confidence: 99%